Association of Guideline‐concordant Acute Asthma Care in the Emergency Department With Shorter Hospital Length of Stay: A Multicenter Observational Study. (13th April 2016) - Hasegawa, Kohei; Brenner, Barry E.; Nowak, Richard M.; Trent, Stacy A.; Herrera, Vivian; Gabriel, Susan; Bittner, Jane C.; Camargo, Carlos A.
Abstract: Objectives: The objectives were to determine whether guideline‐concordant emergency department (ED) management of acute asthma is associated with a shorter hospital length of stay (LOS) among patients hospitalized for asthma. Methods: A multicenter chart review study of patients aged 2–54 years who were hospitalized for acute asthma at one of the 25 U.S. hospitals during 2012–2013. Based on level A recommendations from national asthma guidelines, we derived four process measures of ED treatment before hospitalization: inhaled β‐agonists, inhaled anticholinergic agents, systemic corticosteroids, and lack of methylxanthines. The outcome measure was hospital LOS. Results: Among 854 ED patients subsequently hospitalized for acute asthma, 532 patients (62%) received care perfectly concordant with the four process measures in the ED. Overall, the median hospital LOS was 2 days (interquartile range = 1–3 days). In the multivariable negative binomial model, patients who received perfectly concordant ED asthma care had a significantly shorter hospital LOS (−17%, 95% confidence interval [CI] = −27% to −5%, p = 0.006), compared to other patients. In the mediation analysis, the direct effect of guideline‐concordant ED asthma care on hospital LOS was similar to that of primary analysis (−16%, 95% CI = −27% to −5%, p = 0.005). By contrast, the indirect effect mediated by quality of inpatient asthma care was not significant, indicating that the effect of ED asthma care on hospital LOS was mediated through pathways other than quality of inpatient care. Conclusion: In this multicenter observational study, patients who received perfectly concordant asthma care in the ED had a shorter hospital LOS. Our findings encourage further adoption of guideline‐recommended emergency asthma care to improve patient outcomes.